IMPACT OF SMALL BOWEL CAPSULE ENDOSCOPY IN IRON DEFICIENCY ANEMIA: INFLUENCE OF PATIENT’SAGE ON DIAGNOSTIC YIELD - XAVIER,Sofia (2018)
ABSTRACT BACKGROUND: Iron deficiency anemia remains one of the main indications to perform small bowel capsule endoscopy. Literature suggests that diagnostic yield is influenced by patient’s age but with conflicting results regarding age cutoff. OBJECTIVE: We aimed to clarify the differences in diagnostic yield and incidence of specific findings according to age. METHODS: Retrospective single-center study including 118 patients performing small bowel capsule endoscopy in the study of iron deficiency anemia. Videos were reviewed and small bowel findings that may account for anemia were reported. Incomplete examinations were excluded. Findings were compared between patients ≤60 and >60 years. RESULTS: Patients had a mean age of 58 years old (SD ±17.9) with 69.5% females (n=82). The overall diagnostic yield was 49% (58/118), being higher among patients >60 years (36/60, diagnostic yield 60%) than those ≤60 years (20/58, diagnostic yield 34%), (P<0.01). Angioectasias were more frequent in patients >60 years (45% vs 9%, P<0.01). Patients ≤60 years presented more frequently significant inflammation (Lewis score >135 in 10.3% vs 1.7%, P<0.05) and other non-vascular lesions (24% vs 10%, P=0.04). CONCLUSION: In our cohort small bowel capsule endoscopy diagnosed clinically relevant findings in the setting of iron deficiency anemia in almost half the patients. Diagnostic yield was higher in patients older than 60 years (60%), with vascular lesions being more frequent in this age group. Despite the lower diagnostic yield in patients ≤60 years, significant pathology was also found in this age group, mainly of inflammatory type.